An electrochemical cell with sapphire windows for operando synchrotron X‐ray powder diffraction and spectroscopy studies of high‐power and high‐voltage electrodes for metal‐ion batteries. (6th February 2018) - Drozhzhin, Oleg A.; Tereshchenko, Ivan V.; Emerich, Hermann; Antipov, Evgeny V.; Abakumov, Artem M.; Chernyshov, Dmitry
Abstract : A novel operando electrochemical cell with single‐crystal sapphire X‐ray windows has been designed for and successfully applied to the investigation of phase transformations and the valence states of the cations in high‐power and high‐voltage cathode materials for Li‐ion batteries. Abstract : A new multi‐purpose operando electrochemical cell was designed, constructed and tested on the Swiss–Norwegian Beamlines BM01 and BM31 at the European Synchrotron Radiation Facility. Single‐crystal sapphire X‐ray windows provide a good signal‐to‐noise ratio, excellent electrochemical contact because of the constant pressure between the electrodes, and perfect electrochemical stability at high potentials due to the inert and non‐conductive nature of sapphire. Examination of the phase transformations in the Li1– x Fe0.5 Mn0.5 PO4 positive electrode (cathode) material at C/2 and 10C charge and discharge rates, and a study of the valence state of the Ni cations in the Li1– x Ni0.5 Mn1.5 O4 cathode material for Li‐ion batteries, revealed the applicability of this novel cell design to diffraction and spectroscopic investigations of high‐power/high‐voltage electrodes for metal‐ion batteries.